‘5 Minutes Mindful Breathing’ Smartphone Application for Reduction of Perceived Distress: A Pilot Study - Ng, Chong Guan; Tan, Seng Beng; Zhang, Melvyn; Ho, Roger; Low, Sue-Yin; Ng, Yit Han (Asian Pacific Journal of Cancer Care, 2020)
Background: We have found our 5-minute mindful breathing technique to be effective in reducing distress in palliative cancer patients. As palliative cancer patients tend to experience high levels of distress, the integration of this technique into a smartphone-based application could be a viable intervention option for these patients as well as their caregivers. Objective: We aim to further examine the efficacy of our mindful breathing module on distress reduction within the context of a smartphone-based application for palliative cancer patients and caregivers over a seven day period. We hypothesized that the intervention group (access to mindful breathing module) would have significantly greater distress regulation than the control group (access to soothing music) over seven days of using the smartphone-based application. Methods: 35 subjects were recruited from the palliative care ward at University Malaya Medical Centre (UMMC) and randomly assigned to either the control (access to soothing music) or intervention (access to mindful breathing module) group respectively. They then used and followed instructions as per the smartphone-based application for seven days. Results: While both groups reported a reduction in distress in using the application, there was no significant difference in reported distress levels between those who had access to the mindful breathing module and those who had access to only soothing music over the seven days. Our hypothesis was not supported. Conclusion: Although not significantly greater than the control group, the intervention group reported a reduction in distress using the smartphone application, which suggests that the integration of mindfulness and smartphone applications could potentially play a role in future distress reduction for patients and caregivers in view of its accessibility, ease of administration and anonymity.